Dean flow assisted cell ordering system for lipid profiling in single-cells using mass spectrometry. Issue 21 (2nd February 2018) - Huang, Qiushi; Mao, Sifeng; Khan, Mashooq; Zhou, Lin; Lin, Jin-Ming
Abstract : A Dean flow assisted ordering system connected to an ESI-MS to identify single-cells in a subpopulation by lipid profiling. Abstract : This study describes a novel Dean flow assisted cell ordering system which is connected to an electrospray ionization-mass spectrometer for the detection of lipids in a single-cell. This platform provides a facile method for direct analysis of label-free lipids in single-cells and significantly improves the efficiency of single-cell mass spectrometry.